2005
DOI: 10.1039/b503374h
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial oxygen in oxygen-stoichiometric apatites

Abstract: Several oxy-apatite materials La 102x Sr x (TO 4 ) 6 O 320.5x (T = Ge, Si; 102x = 9.00, 8.80, 8.65 and 8.00) and La 9.33 (Si 12x Ge x O 4 ) 6 O 2 (x = 0, 0.5, 0.67) have been prepared as highly crystalline phases. The impedance study showed that all samples are oxide ion conductors. However, bulk conductivities changed by more than 2 orders of magnitude at a given temperature for some compositions. A thorough study on the oxygen sublattices for oxygen-stoichiometric oxy-apatites has been carried out. Constant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
118
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(138 citation statements)
references
References 45 publications
17
118
1
1
Order By: Relevance
“…1(b). Such an interaction between SiO 4 and interstitial oxygen ion was also pointed out experimentally by 29 Si NMR measurements for stoichiometric La 9.33 (SiO 4 ) 6 O 2 and oxygen-excess La 9.67 (SiO 4 ) 6 -O 2.5 .…”
Section: Low-energy Interstitial Sitessupporting
confidence: 65%
“…1(b). Such an interaction between SiO 4 and interstitial oxygen ion was also pointed out experimentally by 29 Si NMR measurements for stoichiometric La 9.33 (SiO 4 ) 6 O 2 and oxygen-excess La 9.67 (SiO 4 ) 6 -O 2.5 .…”
Section: Low-energy Interstitial Sitessupporting
confidence: 65%
“…Experimental studies have provided confirmation of this position, with Leon-Reina et al showing occupation of a similar site in neutron diffraction studies of the La 9.33+x (Si/Ge) 6 [21][22][23][24]. Moreover, the modelling results further suggested a complex sinusoidal conduction pathway down the channels.…”
Section: Introductionmentioning
confidence: 69%
“…In terms of doping studies, a wide range of dopants have been reported [17,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], Rare earth site: Mg, Ca, Sr, Ba, Bi, Mn, Co, Ni, Cu Si site: Ge, Ti, P, B, Al, Ga, Mn, Co, Fe, Mg, Zn, Ni, Cu Initial studies showed that doping with lower valent ions, e.g. B 3+ , Al 3+ , Ga 3+ , on the Si site, while maintaining oxygen stoichiometry, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Their structure may be described in terms of an (Ln/A) 4-x (Si/GeO 4 ) 6 framework, with the remaining (La/A) 6 O 2 units accommodated in the channels within the 4 framework. In these systems, the oxide ion conduction process has been shown to proceed via a mechanism involving interstitial oxide ions, which are present as a result of either oxygen hyperstoichiometry (x>0) in La 8+x Sr 2-x (Si/Ge) 6 With regard to the location of the interstitial oxide ions, computer modelling studies have predicted that for the silicates the most favourable interstitial oxide ion site is at the periphery of the oxide ion channels neighbouring the SiO 4 groups, which has been supported by neutron diffraction, 29 Si NMR, and Raman studies [14,15,17,27,36]. For the germanates, both modelling and neutron diffraction studies also indicate an interstitial position neighbouring the GeO 4 tetrahedra, although in this case the interstitial oxide ion is more closely associated, leading to five coordinate Ge [21,26].…”
Section: Introductionmentioning
confidence: 85%